Towards Flexible Workplace Governance: employment rights, dispute resolution and social partnership in the Irish Republic - Teague, Paul (Trinity COllege Dublin, 2005)
Workplace conflict is part and parcel of economic life. If disputes at work are not properly addressed, they can get out of hand with potentially far reaching adverse consequences for employers and employees. A well-designed system of workplace governance can ease this problem by creating procedures that settle disputes speedily and fairly. This paper argues that the dispute resolution system in the Republic of Ireland must adopt the principles of flexible workplace governance if it is to remain effective at solving disputes in the context of a rapidly changing economy and labour market. To diffuse the principles of flexible workplace governance, the institutions associated with dispute resolution in Ireland must address a number of challenges. The paper suggests a number of institutional innovations to promote modern high reliability conflict resolution arrangements. The paper concludes that the employment dispute resolution in the Republic of Ireland is well placed to address these challenges.
Keywords: Public Policy; Social partnership; Ireland